2007
DOI: 10.4049/jimmunol.178.8.5312
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Mkp-1 Enhances the Host Inflammatory Responses to Gram-Positive Bacteria

Abstract: MAPK phosphatase (MKP)-1 is an archetypal member of the dual specificity protein phosphatase family that dephosphorylates MAPK. We have previously demonstrated that MKP-1 acts as a negative regulator of p38 and JNK in immortalized macrophages after stimulation with peptidoglycan isolated from Gram-positive bacteria. To define the physiological function of MKP-1 during Gram-positive bacterial infection, we studied the innate immune responses to Gram-positive bacteria using Mkp-1 knockout (KO) mice. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
92
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 47 publications
10
92
2
Order By: Relevance
“…Analysis of the lungs and livers of the mice have indicated that iNOS expression levels were substantially increased in LPS-challenged MKP-1 knockout mice relative to similarly treated wild-type mice (Zhao and Liu, unpublished observations). Additionally, in response to components of Staphylococcus aureus (a Grampositive bacteria), MKP-1 knockout mice also suffered more severe inflammatory injuries to a number of vital organs compared to wild-type mice [60]. Massive neutrophil infiltration, pulmonary edema, liver injury, and kidney dysfunction were also observed in the treated MKP-1 knockout mice [60].…”
Section: In Vivo Function Of Mkp-1 In the Inflammatory Response To Bamentioning
confidence: 89%
See 2 more Smart Citations
“…Analysis of the lungs and livers of the mice have indicated that iNOS expression levels were substantially increased in LPS-challenged MKP-1 knockout mice relative to similarly treated wild-type mice (Zhao and Liu, unpublished observations). Additionally, in response to components of Staphylococcus aureus (a Grampositive bacteria), MKP-1 knockout mice also suffered more severe inflammatory injuries to a number of vital organs compared to wild-type mice [60]. Massive neutrophil infiltration, pulmonary edema, liver injury, and kidney dysfunction were also observed in the treated MKP-1 knockout mice [60].…”
Section: In Vivo Function Of Mkp-1 In the Inflammatory Response To Bamentioning
confidence: 89%
“…Additionally, in response to components of Staphylococcus aureus (a Grampositive bacteria), MKP-1 knockout mice also suffered more severe inflammatory injuries to a number of vital organs compared to wild-type mice [60]. Massive neutrophil infiltration, pulmonary edema, liver injury, and kidney dysfunction were also observed in the treated MKP-1 knockout mice [60]. Consequently, MKP-1 knockout mice exhibited significantly elevated mortality relative to similarly treated wild-type mice [60].…”
Section: In Vivo Function Of Mkp-1 In the Inflammatory Response To Bamentioning
confidence: 90%
See 1 more Smart Citation
“…Members of the MKP family mediate dephosphorylation of threonine/serine and tyrosine residues within the MAPK activation motif, which is sufficient for total enzymatic inactivation (36). Other macrophage activating agents, such as LPS, induce strong levels of expression of MKP-1 (37) which contribute to attenuate proinflammatory responses mediated by LPS-induced MAPK activation (38,39). We hypothesize that repression of MKPs might be necessary to ensure adequate prolonged MAPK activity necessary for stabilizing transcripts involved in the biological response to IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial load or survival rates (when infected by Staphylococcus aureus) were reported to remain unaffected by the DUSP1 deletion, but the tissue damage and immune cell activation and recruitment were substantially potentiated (96). Similar to SHP-1, the DUSP1-mediated iNOS inhibition is also tightly synchronized with the up-regulation of competing arginase pathway.…”
Section: Dusp1 (Mkp-1) Knock-out Leads To An Increase In No Productionmentioning
confidence: 72%